2021
DOI: 10.1097/lbr.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Investigations for the Diagnosis of Malignant Pleural Effusion in Non–small Cell Lung Cancer

Abstract: Lung cancer is the current leading cause of cancer-related deaths worldwide, and malignant pleural effusion, an indicator of the advanced stage of this disease, portends a poor prognosis. Thus, making an accurate diagnosis of malignant pleural effusion is of paramount importance. During the past decade, the prognosis of patients with advanced non–small cell lung cancer has improved substantially, especially in those treated with targeted therapy and immunotherapy. The use of pleural fluid cytology should not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Previously, the diagnosis of pleural effusion was often made by pleural effusion exfoliative cytology, which has good specificity but is limited in clinical use due to the complexity of the procedure. 22 Previous studies 23,24 have revealed that tumor development stimulates the increase of the level of tumor markers, which are released into the blood, and most of them will remain in the tissue fluid around the tumor. Therefore, the positive rate of tumor markers in histological detection is higher than that in blood sample detection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the diagnosis of pleural effusion was often made by pleural effusion exfoliative cytology, which has good specificity but is limited in clinical use due to the complexity of the procedure. 22 Previous studies 23,24 have revealed that tumor development stimulates the increase of the level of tumor markers, which are released into the blood, and most of them will remain in the tissue fluid around the tumor. Therefore, the positive rate of tumor markers in histological detection is higher than that in blood sample detection.…”
Section: Discussionmentioning
confidence: 99%
“…They found the sensitivity of cytologic smears in diagnosing MPEs to be 48% while it was 59.2% for cell blocks with or without cytologic smear. Furthermore, with sufficient cellularity, cytologic samples may be utilized for molecular profiling which may obviate the need for additional biopsies [17,18]. For example, next-generation sequencing on pleural fluid is possible when the tumor fraction of the specimen is >10% while immunohistochemistry and fluorescence in situ hybridization require 50–100 tumor nuclei [19].…”
Section: Thoracentesismentioning
confidence: 99%
“…cytologic samples may be utilized for molecular profiling which may obviate the need for additional biopsies [17,18]. For example, next-generation sequencing on pleural fluid is possible when the tumor fraction of the specimen is >10% while immunohistochemistry and fluorescence in situ hybridization require 50-100 tumor nuclei [19].…”
Section: Primary Cancer Pf Sensitivitymentioning
confidence: 99%
“…The first fraction is cell sediment, used for cytology, and the second is cell-free supernatant, mainly used for biochemical analyses. The biggest challenge is the clarification of the neoplastic origin of the pleural effusion, which is achieved by cytomorphological analyses that have sufficient sensitivity to identify the exact cellular composition and prove the presence of malignant cells [ 8 , 9 ]. Effusion derived tumor cells enriched for testing can be the subject for phenotypic studies (flow cytometry), and furthermore, cell-block processing of the sediment could provide the tissue for the analysis, similar to formaldehyde-fixed and paraffin-embedded (FFPE) sample [10] .…”
Section: Introductionmentioning
confidence: 99%